2020
DOI: 10.3390/nano11010005
|View full text |Cite
|
Sign up to set email alerts
|

Polycarbonate/Titania Hybrid Films with Localized Photo-Induced Magnetic-Phase Transition

Abstract: Materials that exhibit the photo-induced magnetic-phase transition of titania are receiving significant attention because they can be easily switched between diamagnetism and paramagnetism by UV irradiation. However, it is difficult to store photo-induced titanium (Ti3+) in air because of its easy oxidation upon oxygen exposure. In this study, titania/polycarbonate hybrid films were prepared using linear 1,6-hexanediol (PHMCD), cyclic 1,4-cyclohexanedimethanol (PCHCD), or their copolymerized carbonate oligomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Despite its excellent magnetic properties, Ti(III) is easily oxidized in the presence of oxygen and cannot withstand long-term use, which is a new problem. Hara et al [84] exploited the packing effect of the cyclohexane skeleton to control the oxygen permeability. The lifetime of Ti(III) in polycarbonate (PC), which does not have a cyclohexane skeleton, was ~2 h, but by nanodispersing titania in PC with a cyclohexane skeleton, they succeeded in extending the lifetime to ~10 d, which is 120 times longer than previously obtained.…”
Section: Creation Of Functional Hybrids In the Presence Of Ionic Liquidsmentioning
confidence: 99%
“…Despite its excellent magnetic properties, Ti(III) is easily oxidized in the presence of oxygen and cannot withstand long-term use, which is a new problem. Hara et al [84] exploited the packing effect of the cyclohexane skeleton to control the oxygen permeability. The lifetime of Ti(III) in polycarbonate (PC), which does not have a cyclohexane skeleton, was ~2 h, but by nanodispersing titania in PC with a cyclohexane skeleton, they succeeded in extending the lifetime to ~10 d, which is 120 times longer than previously obtained.…”
Section: Creation Of Functional Hybrids In the Presence Of Ionic Liquidsmentioning
confidence: 99%
“…Partially tuning the magnetic susceptibility, rather than changing the magnetic susceptibility of the entire material, could enhance utility in magnetic storage media. [33][34][35][36][37] The order of nanoparticles and polymer crystals in a polymer matrix is controlled by shape memory polymers (SMPs). [38][39][40][41] SMPs are an emerging class of intelligent materials that deform temporarily and change shape, but recover their original shape under environmental stimuli, such as heat, 42,43 light, 44,45 and an electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Partially tuning the magnetic susceptibility, rather than changing the magnetic susceptibility of the entire material, could enhance utility in magnetic storage media. 33–37…”
Section: Introductionmentioning
confidence: 99%
“…To introduce double-network polymers into a normal molding process, it is beneficial to generate cross-linking points after the molding process. The modular patterning of films using photoreactions can add cross-linking points after deposition. For example, Clet et al demonstrated a precise microscale patterning to modify the modulus of silicone elastomers . Furthermore, Sugimoto et al reported that by designing heat-cross-linking and photo-cross-linking parts, an increase in the Young’s modulus by more than 2 orders of magnitude was achieved by performing a photo-cross-linking process after a normal elastomer manufacturing heat process .…”
mentioning
confidence: 99%